Screening of gestational diabetes mellitus: comparison of glucose challenge test done in non fasting state (DIPSI criteria) and fasting state (WHO criteria): a prospective study - Ardhapurkar, Surabhi S.; Kore, Shailesh J.; Supe, Pradnya A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The recent data shows 16.55% prevalence of gestational diabetes mellitus in India. Hence universal screening has become important and we need a simple procedure which is economical and feasible to perform in the Indian context. The comparison of screening methods for gestational diabetes mellitus by 75 gm oral glucose challenge testing done in fasting state (WHO) and non-fasting (DIPSI) state was done. Methods: Cross sectional prospective study done on 225 antenatal women between 20-24 weeks coming to tertiary level hospital in a single working unit were included. They were subjected to two screening glucose challenge tests for detection of gestational diabetes mellitus. Results of glucose challenge tests using 75 gm of anhydrous glucose done in fasting and non fasting state were compared. Values of standard 100 gm oral glucose tolerance test done were considered gold standard. Results: The prevalence of gestational diabetes mellitus was found to be 12.4% by oral glucose tolerance testing. Glucose challenge test with 75 gm done in fasting state was abnormal in 14.7% and abnormal in 15.6% done in non fasting state. The sensitivity of 75 gm GCT done in fasting was 60.7% and the sensitivity of 75 gm GCT done in non fasting state was 67.9%. The specificity of 75 gm GCT done in fasting state was 91.9% and the specificity of 75 gm GCT done in non fasting state was 91.9%. Conclusions: Sensitivity and specificity of the screening tests done by 75 gm GCT done in non fasting state is comparable with screening done in fasting state. Screening done by 75 gm GCT done in non fasting state is convenient and more feasible in Indian setup.